Characterization of LCR Parallel-Type Electromagnetic Shunt Damper for Superconducting Magnetic Levitation - Kentaro Fujita; Toshihiko Sugiura (Actuators, 2022)
This study investigated the effect of electromagnetic shunt dampers on the resonance amplitude reduction in a superconducting magnetic levitation system. There are two types of electromagnetic shunt dampers, series type and parallel type, depending on the configuration of the electric circuit, and their damping characteristics may differ depending on the external resistance value in the circuit. In this study, after discussing the vibration-suppression effects of both types according to the governing equations, vibration experiments were conducted using both dampers with different resistance values. As a result, it was confirmed that, for the larger resistance value, the amplitude reduction effect is smaller in the series-type damper, while it remained high in the parallel type. We also performed numerical integrations, including the nonlinearity of magnetic force in the superconducting magnetic levitation system. As a result, it was numerically confirmed that the parallel-type damper can also be expected to reduce amplitude at a resonance caused by nonlinearity.